Reconstruction of climatic events from the 16th century in Transylvania: interdisciplinary analysis based on historical sources - Gaceu, Ovidiu Răzvan; Caciora, Tudor; Baias, Ștefan; Morar, Cezar; Dudaș, Mihai; Stupariu, Marius; Maxim, Maria (Frontiers in Climate, 2025)
IntroductionUnderstanding past climate variability is essential for interpreting current and future climate trends, particularly during defining climate periods for the past two millennia, such as the Little Ice Age, which had significant socio-economic impacts.MethodsThe present study uses an interdisciplinary approach, analyzing written documents such as chronicles, diaries, and official records to extract data related to climate events in the 16th century in Transylvania (on the current territory of Romania). The obtained results were processed using statistical techniques to reconstruct the evolution of the weather during the respective period.Results and discussionThe study identifies multiple pieces of evidence associated with extreme weather events, including 40 unusually warm summers and several years of excess precipitation or drought. In particular, the period 1,527–1544 was marked by intense heat and droughts, severely affecting agriculture and causing famine. In contrast, the second half of the century is defined by increased rainfall, with numerous reports of flooding and excessive rain, particularly in the 1590s. These extreme climatic events profoundly affected society, contributing to food shortages and increased mortality from starvation and diseases (especially the plague). At the same time, compared to the territory of Western Europe, in Transylvania, heat waves and droughts were more frequent in the first half of the 16th century, while in Western Europe, these climatic phenomena were more sporadic and less intense. Finally, the manuscript emphasizes the significant role of the climate in shaping the historical and socio-economic landscape of Transylvania in the 16th century, offering perspectives on the complex interactions between the climate and the human component.